Comparative analysis reveals the species-specific genetic determinants of ACE2 required for SARS-CoV-2 entry. - Wenlin Ren; Yunkai Zhu; Yuyan Wang; Hongyang Shi; Yin Yu; Gaowei Hu; Fei Feng; Xiaomin Zhao; Jun Lan; Jianping Wu; Devin J Kenney; Florian Douam; et al. (PLoS Pathogens)
Coronavirus interaction with its viral receptor is a primary genetic determinant of host range and tissue tropism. SARS-CoV-2 utilizes ACE2 as the receptor to enter host cell in a species-specific manner. We and others have previously shown that ACE2 orthologs from New World monkey, koala and mouse cannot interact with SARS-CoV-2 to mediate viral entry, and this defect can be restored by humanization of the restrictive residues in New World monkey ACE2. To better understand the genetic determinants behind the ability of ACE2 orthologs to support viral entry, we compared koala and mouse ACE2 sequences with that of human and identified the key residues in koala and mouse ACE2 that restrict viral receptor activity. Humanization of these critical residues rendered both koala and mouse ACE2 capable of binding the spike protein and facilitating viral entry. Our study shed more lights into the genetic determinants of ACE2 as the functional receptor of SARS-CoV-2, which facilitates our understanding of viral entry.